Macroeconomic Effects of the Anticipation and Implementation of Tax Changes in Germany: Evidence from a Narrative Account - Désirée I. Christofzik; Angela Fuest; Robin Jessen (Institute of Labor Economics (IZA), 2024)
This paper quantifies the dynamic macroeconomic effects of tax changes in Germany, allowing for anticipation effects of preannounced tax reforms. Identification is achieved using a narrative approach, which provides information about the timing of tax reforms. An anticipated cut in taxes has a positive effect on output with a peak multiplier of 1.7, observed not until nine quarters after implementation. This positive effect is accompanied by significant negative anticipation effects on output, consumption, investment, hours worked, and wages. Our results suggest that policy makers should take anticipation effects into account when implementing fiscal policy measures.
Keywords: H20; H30; E32; E62; 330; tax policy; anticipation effects; fiscal policy